2016
DOI: 10.1371/journal.pone.0155981
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Water Collection Labor among Women and Children in 24 Sub-Saharan African Countries

Abstract: BackgroundIt is estimated that more than two-thirds of the population in sub-Saharan Africa (SSA) must leave their home to collect water, putting them at risk for a variety of negative health outcomes. There is little research, however, quantifying who is most affected by long water collection times.ObjectivesThis study aims to a) describe gender differences in water collection labor among both adults and children (< 15 years of age) in the households (HHs) that report spending more than 30 minutes collecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(149 citation statements)
references
References 21 publications
6
141
0
2
Order By: Relevance
“…These findings also support the works of Khaka et al, (2006) who found out that 330 million people in Africa are living under water scarcity despite Africa having a huge potential for rain water harvesting. The findings of this study are also in agreement with the UNICEF report of 2017 and Graham, Hirai & Kim, (2016) findings which stated that 25% of Kenyan women and girls spend more than 30 minutes on water collection, just like in other parts of Sub-Saharan Africa.…”
Section: Water Security Status In the Study Areasupporting
confidence: 91%
“…These findings also support the works of Khaka et al, (2006) who found out that 330 million people in Africa are living under water scarcity despite Africa having a huge potential for rain water harvesting. The findings of this study are also in agreement with the UNICEF report of 2017 and Graham, Hirai & Kim, (2016) findings which stated that 25% of Kenyan women and girls spend more than 30 minutes on water collection, just like in other parts of Sub-Saharan Africa.…”
Section: Water Security Status In the Study Areasupporting
confidence: 91%
“…Indeed, it is demonstrated that, when the plot is closer to the home (less than 500 m), generally women spend less time cultivating it and are more motivated. Some authors [68,69] showed also a strong connection between the distance of the water source from the household (and the related time dedicated to women and children to collect water) and its positive effects in terms of productivity, nutrition, health and general empowerment, especially if the water source (especially clean water) is located less than 1 km from the village.…”
Section: The Water Gender Indicatorsmentioning
confidence: 99%
“…Time fetching water was recoded into two categories: 0-30 minutes and 31-481 minutes. A cut-off of 30 minutes was used because the literature argues that the total water collection time should be less than 30 minutes for basic access levels [15]. To assess the association between community water supply and type of water used for drinking, washing and sanitation types, chi-square analyses were conducted.…”
Section: Methodsologymentioning
confidence: 99%